Interplay of multimorbidity and polypharmacy on a community dwelling frail elderly cohort in the peri-urban slums of Delhi, India - Panda, Meely (J Family Med Prim Care, 2020)
The United Nations Population Fund suggests that the number of elderly persons is expected to grow to 173 million by 2026. The aging phase is further made adverse by conditions such as failty, multimorbidity and polypharmacy. AIM: To assess the status and associates of frailty among elderly (>60 years) residing in a peri-urban slum area in Delhi by using the EDMONSTON Frail scale and evaluate the interplay of multimorbidity (MM) and polypharmacy (PP) on the frail pre-frail spectrum of the community-dwelling elderly cohort. METHOD: A community study from Dec 2018 till July 2019 with a sample size of 300 participants who were willing and consented to the study. Frailty was assessed and the STOP criteria was used for PP assessment. RESULT: There were 76 frail, 51 pre-frail, and 173 non-frail elderly. A higher prevalence (51%) of multimorbidity among the pre-frails and a higher probability (74%) of polypharmacy among the frails were found. Of the total in the frail-prefrail spectrum (127), 29.1% had multimorbidity (MM) and 39.4% had polypharmacy (PP). MM and PP were significantly higher among the old. Factors such as sex, marriage, loneliness, social circle, and education also had a positive bearing on the frailty-prefrailty spectrum. The working group had an increased (86%) probability of PP with statistical significance. Regression analysis depicted significant increased odds of MM and PP among female, illiterate, very old, lone, and single subjects. DISCUSSION AND CONCLUSION: Thus, we recommend earlier and timely intervention for the frail-prefrail which can revert their adversities.